Interannual to century scale climate variability in the European Alps - Wanner, Heinz; Hlozhauser, Hanspeter; Pfister, Christian; Zumbühl, Heinz (ERDKUNDE, 2000)
New sets of proxy and early instrumental data from the European Alps allow deeper insights into climate variability and its underlying processes on varying timescales. The study indicates that periods with different forcing characteristics show specific temperature and precipitation anomalies: Cold and dry winters as well as wet summers during the low solar activity period of the Maunder Minimum, cold summers after tropical volcanic eruptions and warm winters in the recent period with an increasing greenhouse gas concentration. The relation between periods with a prevailing positive or negative mode of the North Atlantic Oscillation (NAO) and this natural or anthropogenic forcing is very complex. At least it can be stated that the negative or meridional mode of NAO dominated during the low solar activity period with the cold and dry winters of the late Maunder Minimum. The advance periods of the two selected Alpine glaciers are obviously driven by characteristic but varying temperature and precipitation courses during winter and summer. It is suggested to call these periods Little Ice Age Type Events (LIATE's).